Comparing Real Wage Rates - Ashenfelter, Orley (American Economic Review, 2012)
A real wage rate is a nominal wage rate divided by the price of a good and is a transparent measure of how much of the good an hour of work buys. It provides an important indicator of the living standards of workers, and also of the productivity of workers. In this paper I set out the conceptual basis for such measures, provide some historical examples, and then provide my own preliminary analysis of a decade long project designed to measure the wages of workers doing the same job in over 60 countries—workers at McDonald's restaurants. The results demonstrate that the wage rates of workers using the same skills and doing the same jobs differ by as much as 10 to 1, and that these gaps declined over the period 2000–2007, but with much less progress since the Great Recession. (JEL C81, C82, D24, J31, N30, O57)